Obama and Bush: their victory and non-victory speeches - Fernández Martínez, Dolores; Trujillo González, Verónica Cristina (Onomázein, 2012)
This article aims to analyse the use of the first person plural, second person and third person references in Obama’s and Bush’s victory speeches. The contrasting circumstances surrounding the election of both presidents were imprinted on discourse through different patterns of personal refe-rences (martin, 1992) and transitivity structures (Halliday, 2004 [1985]). By analysing them this paper will illustrate the social function of individuals in the speeches, as well as the way in which the systematic use of both linguistic devices contributed ultimately to define the role of the speak-ers as presidents of the United States. Whereas Obama’s victory speech centred on the audience and allowed them to feel protagonists, Bush’s anti-triumphant speech ignored them.